A new Paraleptamphopidae (Crustacea Amphipoda) in the burrow of Virilastacus rucapihuelensis (Parastacidae) and surrounding peat bogs. Rudolphia macrodactylus n. gen., n. sp. from southern South America - Grosso, Luis E.; Peralta, Marcela (Zootaxa, 2009)
A new genus and species of a chilean Paraleptamphopidae is described. Rudolphia n. gen. shares eleven characters with the family diagnosis sensu Bousfield, 1983. The diagnosis of the new genus is: A1 and A2 long; A1 equal to length of body, A1 inner flagellum scale shaped, calceoli gammarid-type in males only; Mx1 asymmetrical; Gn1 propodus mittenlike, palmar index = 1.81; Gn2 carpus longer than Gn1, palmar index = 2.39; coxal gills: P2–5 and 7 bilobate, P6 ovoid; dactyls of pereopods very long; Pleopods multiarticulate, Pl 2 sexually dimorphic; Uropods birami, rami uniarticulate, Ur1 and Ur2 exopodites scarcely shorter than endopodites, Ur1 peduncle longer than rami, Ur2 resembling Ur1 but much shorter, Ur3 subequal in length to Ur2, Ur3 peduncle shorter than rami, rami acuminated of equal length, with pairs of a bifid and a plumose setae; Telson cleft halfway. Rudolphia macrodactylus n. sp. is the first discovery of Paraleptamphopidae sp. out of New Zealand. A cladistic analysis allows us support that Paraleptamphopidae clade was differentiated before the New ZealandSouth America separation (80–85 mya).